Progress in the Study of Dry Shrinkage Deformation and Drying Stress of Raw Bamboo - Jiayi Zhu; Lin Yang (BioResources)
Bamboo is a sustainable material that supports carbon sequestration and helps address the imbalance of timber supply vs. demand. Drying is a crucial step in bamboo processing, in the course of which shrinkage and stress accumulation can lead to defects such as cracking and deformation. Understanding stress and strain development during drying is critical for improving bamboo processing. This review paper explores bamboo’s gradient structure and moisture migration characteristics, focusing on the mechanisms behind shrinkage strain formation and the sources of stress. It reviews literature on bamboo drying and cellular structural changes, evaluating the evolution of stress and strain testing methods, from traditional sectioning techniques to advanced methods such as digital imaging and acoustic emission. The paper also summarizes progress in stress-strain research at both macroscopic and cellular scales. Current challenges include species-specific shrinkage variations, limitations in measurement techniques, and insufficient research on shrinkage above the fiber saturation point. To address these issues, the study recommends developing universal theoretical models, employing advanced detection technologies, comparing shrinkage patterns between bamboo culms and nodes, exploring drying stress composition, and adopting multi-scale research approaches. These strategies aim to enhance the quality of bamboo processing and promote higher-value applications within the industry.